Imaging Red Supergiants with VLT/SPHERE/ZIMPOL. Issue Volume 14:Issue S343(2019) (August 2018) - Cannon, E.; Montargès, M.; Decin, L.; de Koter, A.
Abstract: Using the VLT-SPHERE/ZIMPOL adaptive optics imaging polarimeter, images of a sample of nearby red supergiants (RSGs) were obtained in multiple filters. From these data, we obtain information on geometrical structures in the inner wind, the onset radius and spatial distribution of dust grains as well as dust properties such as grain size. As dust grains may play a role in initiating and/or driving the outflow, this could provide us with clues as to the wind driving mechanism.